Odpowiedź :
Odpowiedź:
[tex]a)\ \ 5a-(3a+6)+5=5a-3a-6+5=2a-1\\\\b)\ \ -8x+(2y+x)=-8x+2y+x=-7x+2y\\\\c)\ \ 2a-7b+(5a-2b)=2a-7b+5a-2b=7a-9b\\\\d)\ \ -2x+8y-(6x-7y)=-2x+8y-6x+7y=-8x+15y\\\\e)\ \ (-7a-c)-(4a-2c)=-7a-c-4a+2c=-11a+c\\\\f)\ \ (5x+4xy+5y)-(2x-xy-3y)+(-x+2xy+y)=\\\\=5x+4xy+5y-2x+xy+3y-x+2xy+y=2x+7xy+9y\\\\g)\ \ (2x^2+3x+4)-(-3x^2-5x+1)-(4x^2+x-4)=\\\\=2x^2+3x+4+3x^2+5x-1-4x^2-x+4=x^2+7x+7[/tex]
Odpowiedź:
a) 5a -( 3a+6) +5= 5a-3a -6 +5= 2a -1
b) -8x + ( 2y+x)= -8x +2y +x= -7x +2y
c) 2a - 7 b + ( 5a- 2b)= 2a -7b +5a -2b= 7a -9 b
d) -2x + 8 y - ( 6x-7y)= -2x+ 8y -6x +7y= -8x +15y
e) ( - 7a -c) - ( 4a-2c)= -7a-c -4a + 2c= - 11a +c
f) ( 5x +4xy +5y) - ( 2x- xy -3y) + ( -x +2xy +y)=
= 5x +4xy +5y -2x +xy+3y -x +2xy+y= 2x +7xy +9y
g) ( 2x² +3x +4) - ( -3x²-5x +1 ) - ( 4x²+x -4)=
2x²+3x +4 +3x²+5x-1 -4x²-x +4= x²+7x +7
Szczegółowe wyjaśnienie: